Immobilization of Acidithiobacillus ferrooxidans in bacterial cellulose for a more sustainable bioleaching process. Issue 4 (August 2021) - Santaolalla, A.; Gutierrez, J.; Gallastegui, G.; Barona, A.; Rojo, N.
Abstract: This study used bacterial cellulose (BC) as novel support material for Acidithiobacillus ferrooxidans immobilization, with the objective of improving the performance of bioleaching and increasing its sustainability. The BC was synthesized in the laboratory, which allowed selecting the desired size of this highly porous and mechanically resistant material. After bacterial immobilization, the biologically active material (BAM) was used to assess the effect that several operating parameters had on the process (shaking mode and speed, the nutrient medium volume-to-exposed surface area ratio –NMV:ESA-, and Fe 2+ concentration). The influence of dissolved copper and BAM storage was also determined. The results showed that the NMV:ESA ratio conditioned Fe 2+ bio-oxidation time: after 33 h, 60% and 90% of the initial Fe 2+ in the samples was converted, with a 1:0.1 and 1:0.6 ratio, respectively. In addition, Fe 3+ productivity increased 16% when raising the initial Fe 2+ content from 6 to 9 g L −1 . A considerable increase in productivity (from 190 to 223 mg L −1 h −1 ) was also recorded when the shaking speed was increased from 130 to 170 rpm. BAM successfully adapted to the presence of dissolved copper and oxidized Fe 2+ in the presence of up to 30 g Cu 2+ L −1 . Finally, the integrity of the material was not affected by the demanding operating conditions, and bacterial activity was successfully recovered after storage at 4 °C and 22 °C. In sum, biocellulose has proven to be a suitable candidate for A. ferrooxidans immobilization, which could contribute to improving the efficiency of bioleaching. Graphical Abstract: ga1 Highlights: Bacterial cellulose is a new suitable support for A. ferrooxidans immobilization. The optimum operating conditions for reducing bio-oxidation time were established. Fe 3+ productivity of 223 mg L −1 h −1 was achieved at selected operating conditions. The immobilized bacteria were resistant to copper concentrations up to 30 g L −1 . The use of bacterial cellulose enhanced the sustainability of bioleaching process.